2019
DOI: 10.3390/su11061754
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Influencing Factors of Sustainable Development for Traditional Power Generation Groups in a Market by Applying an Extended MCDM Model

Abstract: With the deepening reform of the power market, the external environment of China’s power industry is going through a huge change. China’s traditional power generation groups (TPGGs), with assets all over the country, are, due to a lack of market awareness about energy policies, facing serious challenges in developing competitive advantages, improving power transaction modes, optimizing profit models, and even realizing basic corporate strategies. In this study, we focus on identifying the key factors influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 72 publications
0
16
0
1
Order By: Relevance
“…Figure 1. Flow chart for the energy systems selection decision procedure The criteria set used for multi criteria GDM, conducted for selection of energy systems [6,13,15,18,22,24,26,29,32,36,40] in different countries, is given in Table 1. Table 2 shows the scores used for the assessment of fuzzy linguistic terms.…”
Section: Fuzzy Ahp Methodology For Determining Experts' Weights For Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1. Flow chart for the energy systems selection decision procedure The criteria set used for multi criteria GDM, conducted for selection of energy systems [6,13,15,18,22,24,26,29,32,36,40] in different countries, is given in Table 1. Table 2 shows the scores used for the assessment of fuzzy linguistic terms.…”
Section: Fuzzy Ahp Methodology For Determining Experts' Weights For Cmentioning
confidence: 99%
“…The energy security problem, the rising energy prices, and the other important factors require sustainable development of power generation systems. The application of multi-criteria decision-making (MCDM) approaches [13] can prioritize the importance of the energy systems. On the other hand, the economic growth and social needs will increase the hydrocarbon consumption from 3.4 million BOE (barrels of oil equivalent) to 8.3 million BOE per day shortly.…”
mentioning
confidence: 99%
“…Delphi method had been used in many areas and can be used for any purpose requiring the use of committees [58][59][60][61][62]. Based on many studies, Sourani and Sohail (2015) presented Delphi as useful to (a) obtain accurate information that is unavailable, (b) handle complex problems that require more judgmental analysis, (c) define areas where there is considerable uncertainty and/or a lack of agreed knowledge or disagreement, (d) allow for combining fragmentary perspectives into a collective understanding, (e) model a real-world phenomenon involving a range of viewpoints and for which there is little established quantitative evidence, and (f) highlight topics of concern and assess uncertainty in a quantitative manner [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Purposesmentioning
confidence: 99%
“…More recently, Delphi has been widely used to develop the criteria and indicators in many fields, especially in construction fields [56][57][58][59][60][61][62]; for example, Sourani and Sohail (2015) [63] used the Delphi technique to develop an agreed set of economic sustainability criteria that should be addressed in a procumbent strategy. Moreover, many studies [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] have showed that Delphi can be useful to (a) obtain accurate information that is unavailable, (b) handle complex Sustainability 2019, 11, 3166 3 of 32 problems that require more judgmental analysis, (c) define areas where there is considerable uncertainty and/or a lack of agreed knowledge or disagreement, (d) allow for combining fragmentary perspectives into a collective understanding, (e) model a real world phenomena involving a range of viewpoints and for which there is little established quantitative evidence, and (f) highlight topics of concern and assess uncertainty in a quantitative manner. In particular, based on the summary explained in Appendix A [78][79][80][81][82][83][84], this research accordingly chose the Delphi technique to develop sustainable city indicators (SCIs) for Cambodia through three-round panel surveys.…”
mentioning
confidence: 99%
“…MCDM is widely used not only in research but also in practice. Common methods include TOPSIS [21], VIKOR [22], the correlation degree method [23], the FMEA method [24,25], the fuzzy comprehensive evaluation method (FCEM) [26], genetic algorithm [27], the entropy weight method [28], ANP [29], AHP [30], etc. These methods have specific advantages and applications.…”
Section: Introductionmentioning
confidence: 99%